Virulence genes and antimicrobial susceptibility of lactose-negative and lactose-positive strains of Escherichia coli isolated from pregnant women and neonates - Kaczmarek, Agnieszka; Skowron, Krzysztof; Budzyńska, Anna; Grudlewska, Katarzyna; Gospodarek-Komkowska, Eugenia (Folia microbiologica, 2017)
Escherichia coli can cause serious infections in the neonates and pregnant women. Although E. coli is widely studied, E. coli lactose-negative (lac-) strains have been rarely described before. So, the aim of this study was to compare lac- and lactose-positive (lac+) E. coli strains in respect of antimicrobial susceptibility and the frequency of virulence genes (VGs). The study included 58 lac+ and 58 lac- E. coli strains isolated from pregnant women and neonates. Culture and the results of biochemical reactions were conducted for lac- and lac+ E. coli identification and differentiation. Disc diffusion test was performed to study the antimicrobial susceptibility of the isolates, and PCR was used to detect VGs. Resistance to at least one of the tested antibiotics was found among 14 (25.9%) E. coli lac+ and in 26 (44.9%) E. coli lac- strains. Both lac+ and lac- E. coli strains were mostly resistant to ampicillin (22.4 and 39.7%) and ticarcillin (20.7 and 39.7%). None of the tested strains produced extended-spectrum β-lactamases (ESBLs). Genes fimH, fimA, iutA, sfa/foc, neuC, ibeA, and hlyF were detected, respectively, in 96.6, 82.8, 32.8, 24.1, 22.4, 12.1, and 6.9% of lac+ E. coli strains and in 94.8, 86.2, 48.3, 19.0, 8.6, 8.6, and 1.7% of lac- strains. The antimicrobial susceptibility and the pathogenic potential of both tested groups of E. coli strains are similar. Therefore, omitting E. coli lac- strains as a potential etiological agent of infections may pose a threat to the health and life of both mothers and neonates.
Keywords: Virulence Factors; Anti-Bacterial Agents; bakteriální léková rezistence; Disk Diffusion Antimicrobial Tests; Drug Resistance, Bacterial; Pregnancy Complications, Infectious; techniky typizace bakterií; těhotenství; kojenec; polymerázová řetězová reakce; Polymerase Chain Reaction; Infant; Adult; mladý dospělý; Bacterial Typing Techniques; infekční komplikace v těhotenství; Infant, Newborn; Young Adult; Escherichia coli; ženské pohlaví; novorozenec; Humans; Pregnancy; laktosa; antibakteriální látky; Escherichia coli Infections; dospělí; faktory virulence; Lactose; Female; lidé; infekce vyvolané Escherichia coli; diskové difúzní antimikrobiální testy